Pathobiology of Japanese encephalitis virus infection. (October 2021) - Sharma, Kiran Bala; Vrati, Sudhanshu; Kalia, Manjula
Abstract: Japanese encephalitis virus (JEV) is a flavivirus, spread by the bite of carrier Culex mosquitoes. The subsequent disease caused is Japanese encephalitis (JE), which is the leading global cause of virus-induced encephalitis. The disease is predominant in the entire Asia-Pacific region with the potential of global spread. JEV is highly neuroinvasive with symptoms ranging from mild fever to severe encephalitis and death. One-third of JE infections are fatal, and half of the survivors develop permanent neurological sequelae. Disease prognosis is determined by a series of complex and intertwined signaling events dictated both by the virus and the host. All flaviviruses, including JEV replicate in close association with ER derived membranes by channelizing the protein and lipid components of the ER. This leads to activation of acute stress responses in the infected cell-oxidative stress, ER stress, and autophagy. The host innate immune and inflammatory responses also enter the fray, the components of which are inextricably linked to the cellular stress responses. These are especially crucial in the periphery for dendritic cell maturation and establishment of adaptive immunity. The pathogenesis of JEV is a combination of direct virus induced neuronal cell death and an uncontrolled neuroinflammatory response. Here we provide a comprehensive review of the JEV life cycle and how the cellular stress responses dictate the pathobiology and resulting immune response. We also deliberate on how modulation of these stress pathways could be a potential strategy to develop therapeutic interventions, and define the persisting challenges.